2020
DOI: 10.2188/jea.je20190061
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Marriage and Education on Mortality: A Cross-national Study of Older Japanese and Finnish Men and Women

Abstract: Background: While marriage and education help maintain older adults' health, their joint association with mortality remains unclear. This cross-national study examined the combined effect of marriage and education on the mortality of older Japanese and Finnish adults. Methods: Data on 22,415 Japanese and 11,993 Finnish adults, aged 65-74 years, were obtained from the Japan Gerontological Evaluation Study of 2010-2012 and the Finnish Public Sector Study of 2008-2009 and 2012-2013. We followed up on respondents'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
1
0
2
Order By: Relevance
“…In the present study, age and partner status were the most important predictors of mortality. This is in line with other studies that concluded marital status was significantly associated with mortality (Cerhan & Wallace, 1997;Iecovich et al, 2011;Saito et al, 2020;Stessman et al, 2014). A recent study by Manvelian and Sbarra (2020) showed that having fewer than 4-6 close relationships was associated with higher mortality in older adults that lost their partner.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, age and partner status were the most important predictors of mortality. This is in line with other studies that concluded marital status was significantly associated with mortality (Cerhan & Wallace, 1997;Iecovich et al, 2011;Saito et al, 2020;Stessman et al, 2014). A recent study by Manvelian and Sbarra (2020) showed that having fewer than 4-6 close relationships was associated with higher mortality in older adults that lost their partner.…”
Section: Discussionsupporting
confidence: 91%
“…From the fact that they strongly disagree or strongly agree, they get 1–5 points in 5 stages until they strongly agree, and the total score is 70 points, which means that the higher the score, the higher the HL. Japan has an educational history equal to or higher than that of European countries, and it is expected that the basic HL is high [ 21 , 22 ]. In this survey, we investigated eight items focusing on communicative/critical HL.…”
Section: Methodsmentioning
confidence: 99%
“…Coping diádico X X CCET Amor romântico X X FGL Research, Society andDevelopment, v. 12, n. 2, e14012238481, 2023 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v12i2.38481 currículo, mas, ainda assim, os resultados indicam um efeito dessas intervenções sobre a saúde. Ou seja: trabalhar aspectos da interação do casal pode ser um meio para promover melhorias em outros aspectos da vida, tal como diversas pesquisas de predição indicam (Azimian et al, 2017;Donoho et al, 2015;Liu et al, 2016;Peterson-Post et al, 2014;Recksiedler & Stawski, 2019;Rhobes et al, 2014;Saito et al, 2020;Torvik et al, 2015;Yang et al, 2011).…”
Section: Número Do Artigo Desfechosunclassified
“…Há evidências de que a baixa qualidade da interação pode ser um fator de risco para comportamentos prejudiciais com relação à atividade física e uso do tabaco (Lee et al, 2019), assim como fatores de risco para problemas de saúde, como os cardiovasculares e, até mesmo, para a mortalidade (Donoho et al, 2015;Lee et al, 2019;Robles et al, 2014;Saito et al, 2020;Va et al, 2011). O divórcio, por sua vez, foi associado à saúde subjetiva empobrecida, consumo excessivo de álcool, sofrimento mental, falta de exercícios e tabagismo (Torvik et al, 2015).…”
Section: Introductionunclassified